Metadata access to archival collections on Malay cultural heritage at ATMA: Architecture and proverbs - Supyan Hussin,; Ding, Choo Ming; Kala Kuppusamy, (Universiti Kebangsaan Malaysia, 2004)
This paper is a review of the metadata construction of a large archive of Malay proverbs and still images from N. A. Halim’s collection. The former are textual while the latter are visual. The digital integration of materials that are rightly considered a part of Malay indigenous knowledge hopes to make it possible to retrieve them on the Internet quickly and effectively